2021
DOI: 10.1177/1362168820986936
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pragmatic content in EFL textbooks for young learners in Croatia

Abstract: Pragmatic competence is an essential element of communicative competence, which makes it relevant for speakers of all ages, including young language learners (YLLs). Despite the recognized importance of pragmatics, research of textbooks for adult second language (L2) learners to date has found them lacking in their approach to this key aspect of language. However, there is very little research of pragmatics in textbooks for YLLs, which would provide insight into the extent to which these materials can support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another example comes from Schauer (2019), he examined and found that most speech acts are underrepresented in textbooks, for example, the requesting act accounts for 74% of all instances, but responses takes only 11%. As a result, a great deal of inconsistency in the scope and treatment of pragmatic content providing are extremely lacking (Jakupčević & Ćavar 2021), which will make it harder for learners to notice input, and degrade the effect of acquiring the patterns of natural language use.…”
Section: On Speech Actsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example comes from Schauer (2019), he examined and found that most speech acts are underrepresented in textbooks, for example, the requesting act accounts for 74% of all instances, but responses takes only 11%. As a result, a great deal of inconsistency in the scope and treatment of pragmatic content providing are extremely lacking (Jakupčević & Ćavar 2021), which will make it harder for learners to notice input, and degrade the effect of acquiring the patterns of natural language use.…”
Section: On Speech Actsmentioning
confidence: 99%
“…Textbook is an important source of information and inspiration for many textbook writers and teachers (Jakupčević & Portolan, 2021), so it must be correctly and authentically written to enable students to immerse themselves in acquiring language forms and avoid pragmatic errors. While the current primary school English textbooks in mainland China don't emphasize enough the importance of pragmatic knowledge in textbooks, accordingly teachers cannot be expected to realize the pragmatic need, instead, they focus more on the linguistic knowledge.…”
Section: Pragmatic Featuresmentioning
confidence: 99%
“…Similar to Vollmuth's (2004) study, no responses to expressions of gratitude were found in the materials. Jakupčević and Portolan (2021) examined 18 textbooks that are used in grades 4 to 6 in Croatian primary schools attended by EFL learners aged 9 to 12 years old. The textbooks were published by two Croatian and three international publishing houses between 2013 and 2019.…”
Section: Studies Examining Teaching Materials By Textbook Publishersmentioning
confidence: 99%
“…In the FL context, however, exposure to authentic input can be, at times, a challenge. Indeed, learners in a FL classroom lack real pragmatic input and opportunities for interacting beyond the classroom as the input they receive comes mainly from two main sources: the instructor and course textbooks, which have come under criticism for their failure to provide learners with adequate pragmatic input (Barón, Roquet, Evnitskaya & Navarro 2020;Jakupčević & Ćavar Portolan 2021). The provision of authentic input is necessary for pragmatic development, and that is something that audiovisual material can address comfortably in the FL classroom (Bardovi-Harlig 2019).…”
Section: Audiovisual Inputmentioning
confidence: 99%